Free-living hard ticks (Ixodida: Ixodidae) from three different natural environments of Costa Rica - Montenegro, Víctor M. (2021)
This paper presents data on free-living ticks collected by flagging and using CO2 traps in three natural areas in Costa Rica: Carara National Park (CNP), Palo Verde National Park (PVNP), and a Private Forest Reserve in Sarapiquí (SPR). Data were analyzed calculating aspects of alpha diversity (species richness, entropy; dominance index, and evenness); and for beta diversity, compositional similarity between communities of ticks was also calculated. We collected 12,795 ticks belonging to 10 species: Amblyomma coelebs, Amblyomma dissimile, Amblyomma mixtum, Amblyomma naponense, Amblyomma cf. oblongoguttatum, Amblyomma cf. parvum, Amblyomma sabanerae, Amblyomma tapirellum, Haemaphysalis juxtakochi and Ixodes affinis. The number of species and individuals varied between sites: 5970 ticks were collected in CNP, 4443 in PVNP, and 2382 in SPR. Amblyomma cf. oblongoguttatum and A. cf. parvum were collected at all three sites, but A. mixtum was the most abundant species, even though it was not collected in SPR. Values of alpha diversity were calculated for CNP and SPR, while diversity in PVNP was the lowest of the three locations. Evenness was highest in SPR and lowest in CNP. The only community that presented dominance was PVNP. Beta diversity showed low similarity between the three locations with the lowest being CNP and SPR. For the three localities, estimates of the number of tick species based on presence/absence data was higher using flagging than CO2; and considering the stage of the ticks collected. More larvae were captured using CO2 traps than by flagging, while flagging was better for col- lecting adults. To our knowledge this is the first study in Costa Rica that compares these two sampling methods in three different environmental areas.